Evidence for acute electrophysiological and cognitive changes following routine soccer heading - Di Virgilio, Thomas G.; Howatson, Glyn; Hunter, Angus; Wilson, Lindsay; Stewart, William (Elsevier, 2016)
Introduction: There is growing concern around the effects of concussion and sub-concussive impacts in sport. Routine game-play in soccer involves intentional and repeated head impacts through ball heading. Although heading is frequently cited as a risk to brain health, little data exist regarding the consequences of this activity. This study aims to assess the immediate outcomes of routine football heading using direct and sensitivemeasures of brain function. Methods: Nineteen amateur football players (5 females; age 22± 3 y) headedmachine-projected soccer balls at standardized speeds,modelling routine soccer practice. The primary outcomemeasure of corticomotor inhibition measured using transcranial magnetic stimulation, was assessed prior to heading and repeated immediately, 24 h, 48 h and 2 weeks post-heading. Secondary outcome measures were cortical excitability, postural control, and cognitive function. Results: Immediately following heading an increase in corticomotor inhibition was detected; further to these electrophysiological alterations, measurable reduction memory function were also found. These acute changes appear transient, with values normalizing 24 h post-heading. Discussion: Sub-concussive head impacts routine in soccer heading are associated with immediate, measurable electrophysiological and cognitive impairments. Although these changes in brain function were transient, these effects may signal direct consequences of routine soccer heading on (long-term) brain health which requires further study
Keywords: Sports concussion; Transcranial magnetic stimulation; Sub-concussion; Traumatic brain injury